2001
DOI: 10.1086/322049
|View full text |Cite
|
Sign up to set email alerts
|

SubclinicalLegionellaInfection in Workers Near the Source of a Large Outbreak of Legionnaires Disease

Abstract: A survey was conducted of exhibitors at a 1999 floral trade show, where a whirlpool spa on display caused a large outbreak of legionnaires disease (LD). In total, 742 exhibitors without LD returned a questionnaire on their whereabouts during the fair and their health afterward and supplied blood samples for the detection of IgM and IgG antibodies against Legionella pneumophila. The exhibitors had higher average antibody levels than did the general population. The closer to the whirlpool that the exhibitors wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 14 publications
1
58
1
4
Order By: Relevance
“…These results resemble those of Maesaki et al (9) who reported an outbreak of Legionella pneumonia in a nursing home. Attack rates in outbreaks of Legionella pneumonia are usually low [0.1%-5% of exposed persons develop clinical symptoms (10)] and the development of pneumonia was seen in only one person here. The low attack rate may be due to host factors or differences in exposure (10).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results resemble those of Maesaki et al (9) who reported an outbreak of Legionella pneumonia in a nursing home. Attack rates in outbreaks of Legionella pneumonia are usually low [0.1%-5% of exposed persons develop clinical symptoms (10)] and the development of pneumonia was seen in only one person here. The low attack rate may be due to host factors or differences in exposure (10).…”
Section: Discussionmentioning
confidence: 92%
“…Attack rates in outbreaks of Legionella pneumonia are usually low [0.1%-5% of exposed persons develop clinical symptoms (10)] and the development of pneumonia was seen in only one person here. The low attack rate may be due to host factors or differences in exposure (10). However, especially in places such as nursing homes where many people are susceptible to microbes, strict management practices to reduce microbial contamination of 24-hour bath water are needed to prevent Legionella pneumonia which can sometimes cause severe disease (11).…”
Section: Discussionmentioning
confidence: 92%
“…A nationwide alert for LD cases ensured optimal case finding, thereby decreasing patient selection bias. Furthermore, the conditions for a gold standard were favorable: two national reference laboratories performed all microbiological tests, and Dutch reference titers were calculated using the distribution of antibodies against L. pneumophila serogroup 1 in a large sample from a national serum bank (4). In addition, all available clinical data for the LD patients in this outbreak were recorded centrally.…”
Section: Discussionmentioning
confidence: 99%
“…Robust immune response of a healthy individual normally is sufficient to clear L. pneumophila, making legionellosis largely a disease of people with a compromised immune system (20). Experiments with the mouse model have revealed that immune cells are able to recognize classic L. pneumophila PAMP molecules such as lipopolysaccharide, flagellin, and nucleic acids to mount a robust response (21).…”
mentioning
confidence: 99%